2013
DOI: 10.1542/peds.2013-1076
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Triage for Children With Chronic Illness and Infectious Symptoms

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Children with chronic illnesses tend to be sicker during infections than previously healthy children but are triaged in the same way, even though the validity of triage systems has not yet been evaluated in these chronically sick children. WHAT THIS STUDY ADDS:The performance of the Manchester Triage System was lower for children with a chronic illness than for previously healthy children. Children with cardiovascular illnesses, respiratory illnesses, gastrointestinal illnesses, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 17 publications
4
31
1
5
Order By: Relevance
“…A modified version of the MTS increased the specificity from 78%–79% to 87%, but not the sensitivity (64%), resulting in the reduction of overtriage (47%) without a parallel increase in undertriage (15%) 39. The other two studies assessed subgroups of patients and showed an undertriage rate of 2% in patients levels 1 and 238 and poorer sensitivity (58% vs 74%) and higher undertriage rate (17% vs 11%) in patients with symptoms of infection and chronic disease compared with those without chronic disease 42…”
Section: Resultsmentioning
confidence: 94%
“…A modified version of the MTS increased the specificity from 78%–79% to 87%, but not the sensitivity (64%), resulting in the reduction of overtriage (47%) without a parallel increase in undertriage (15%) 39. The other two studies assessed subgroups of patients and showed an undertriage rate of 2% in patients levels 1 and 238 and poorer sensitivity (58% vs 74%) and higher undertriage rate (17% vs 11%) in patients with symptoms of infection and chronic disease compared with those without chronic disease 42…”
Section: Resultsmentioning
confidence: 94%
“…The Dutch cohort was divided into a cohort of children aged <3 months (the Netherlands <3 months’ cohort) and children aged between 3 and <12 months (the Netherlands >3–12 months’ cohort). In the Dutch cohort we prospectively enrolled all children (1 month to 1 year) presenting with fever at the EDs of the Erasmus MC-Sophia Children’s Hospital (inner city university hospital, 7000 annual paediatric ED visits)25 and the Maasstad Hospital (inner-city teaching hospital, 10 000 paediatric medical emergency consults yearly), Rotterdam (2009–2012), the Netherlands. In both hospitals febrile children were eligible to participate in the study if fever had been noted at home in the 24 hours prior to presentation, if body temperature measured at the ED was ≥38.5°C or ‘fever’ was used as a positive discriminator of the Manchester Triage System.…”
Section: Methodsmentioning
confidence: 99%
“…About 35% of the ED population has chronic co-morbidity. [23] We excluded children with chronic diarrhea (>7 days), severe dehydration with hypovolemic shock, children with vomiting/diarrhea with a focus for another infectious disease (e.g., otitis media, urinary tract infection) and chronically ill children with complex needs.…”
Section: Methodsmentioning
confidence: 99%